Cumhuriyet’e geçiş sürecinde tiyatro (1908-1923) - Öz, Hasan Fehmi (My University, 2003)
Bu Araştırmada Türkiye Cumhuriyeti'nin doğuşu esnasında Türk tiyatrosundaki değişimler incelenmiştir. Bu değişimler sosyal ve iktisadi olarak araştırılmıştır. Osmanlı toplumunun Tiyatro hakkındaki fikirleri ve sosyal değişimler arşiv belgeleriyle ortaya çıkarılmıştır. Tiyatronun Milli Mücadele Dönemindeki etkisi araştırılmıştır. Bu araştırma Başbakanlık Osmanlı Arşivi, süreli yayınlar ve basılı kaynaklara dayanarak hazırlanmıştır. In this investigation, changes at the Turkish Theatre has been investigated during rising up Turkish Republic. These changes have been researched as social and economical. Ottoman Society's ideas about theatre and social changes have been appeared by documents of the archive. Effect of the theatre has been investigated during National Independent Movement, this survey has been prepared based on Ottoman Archive, perlodicals and books. In this investigation, changes at the Turkish Theatre has been investigated during rising up Turkish Republic. These changes have been researched as social and economical. Ottoman Society's ideas about theatre and social changes have been appeared by documents of the archive. Effect of the theatre has been investigated during National Independent Movement, this survey has been prepared based on Ottoman Archive, perlodicals and books.
Keywords: Gösteri sanatları; Sahne gösterileri; Türk Tiyatrosu_1908-1923